Peranan BPOM Dalam Melakukan Pengawasan Terhadap Produk Makanan Kadaluarsa - Farhan Nandiva (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to clarify the role of BPOM in carrying out supervision of food products circulating in the market according to BPOM's supervisory function and how forms of protection for consumers are related to the distribution of expired food using normative juridical research methods. BPOM in supervising food in circulation carries out several types of supervision, including supervision at the time of production, supervision before distribution, supervision during distribution, and legal action or sanctions for those distributing expired food. Regarding consumer protection for expired food, consumers have rights that must be exercised by business actors in accordance with the Consumer Protection Act. To fulfill their rights, consumers can make complaints to BPSK to resolve disputes with business actors as a form of protection. And to reduce the circulation of expired food, efforts must be made from related parties, both from the government, business actors, and consumers. BPOM as an authorized body can carry out tighter and more effective supervision. Business actors are also expected to be aware of the law by fulfilling their obligations as business actors, and consumers must be more observant in paying attention to the expiration date listed on the packaging.